"Not" : Vortrag, gehalten auf der 16. Generalversammlung des Allgemeinen Deutschen Frauenvereins zu Dresden am 29. September 1891 - Lange, Helene, 1848-1930 (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1892)
The need of which Helen Lange speaks in this lecture is a physical and a psychic need, the poverty of both body and soul. She urges her female audience to be more aware of both and to do all that they can to eliminate them, in themselves, as well as in others less fortunate.